PERFORMANCE ANALYSIS OF C I ENGINE FUELLED WITH DIESEL - BIODIESEL (METHYL/ETHYL ESTERS) BLEND OF NON-EDIBLE OIL - Rao, Venkateswara (International Journal of Research -GRANTHAALAYAH, 2016)
High viscosity, poor volatility and heavy chemical structure of vegetable oil are the main constraints to replace diesel fuel. This paper investigates the scope of utilizing biodiesel produced with ethanol and methanol as alcohols in the process of making biodiesel. Experiments were conducted on diesel engine with B20 of methyl and ethyl esters of Pongamia oil (POME20, POEE20), methyl and ethyl esters of Mahua oil (MOME20, MOEE20) and standard diesel fuel separately. The performance and emission characteristic results were compared with diesel fuel. Results indicate that from all the experiments 20% Pongamia oil methyl ester produces 13.2% less power at 3.22% more specific fuel consumption than diesel fuel at maximum load. From the emission results the observation is that slight reduction of hydrocarbon, carbon monoxide and smoke emissions with moderate increase in carbon dioxide emission.